A relação entre a assistência estudantil e o perfil socioeconômico dos estudantes do CCAE - Campus IV da UFPB - Maurício, Ana Cristina Crispim (2021)
The present work seeks to understand the role of student assistance in the university trajectory of students from CCAE, campus IV of UFPB. For this, we have set as a general objective to characterize the relationship between student assistance and the socioeconomic profile of the students of the Campus IV, and establish as specific objectives to describe the process of expansion of higher education which one was responsible for creating the Campus IV of UFPB; draw the profile of the student awarded assistance programs at the CCAE; and present a report with proposals for improvements to the PNAES in the CCAE. To achieve these goals, a survey was conducted out between March and May with 30 students of the CCAE - Unit Rio Tinto, which ones were benefited from student campus aid in the school period 2019.2. To these, an electronic form was sent in which we tried to obtain data regarding the socioeconomic and academic profile, categorize the student within the PNAES and understand how the student assistance actions relate to the socioeconomic profile of the student on campus IV. The analysis of the research data was carried out using the Content Analysis method, which allowed us to discuss the results obtained through inference. Through the results of the research it was possible to observe some common characteristics of the beneficiaries of student assistance on Campus IV, most of them are young people who come from socially vulnerable families, students who, in order to stay at the university, mainly need housing and food. In Campus IV, as in other IFES in Brazil, the Student Assistance does not have the ideal coverage to promote permanence; however, in CCAE, despite the limitations of the program, this public education policy has shown to be of extreme importance in the trajectory of students on this campus.